Association between Islamic religiosity, social support, marriage satisfaction, and postpartum depression in teenage mothers in West Java, Indonesia: A cross-sectional study - Irma Nurbaeti; Kustati Budi Lestari; Moch Syafii (Belitung Raya Foundation, Indonesia, 2023)
Background: Postpartum depression is a prevalent mental health issue among mothers after giving birth. Adolescent mothers are believed to have a higher rate of postpartum depression than adult mothers. However, research on postpartum depression among teenage mothers in Indonesia remains limited. This research gap emphasizes the need for more comprehensive studies to address the mental health and well-being of postpartum mothers in Indonesia, especially among adolescents. Objective: This study aimed to investigate the correlations between Islamic religiosity, social support, marital satisfaction, and postpartum depression in teenage mothers in Indonesia. Methods: A cross-sectional study was conducted involving 203 adolescent postpartum mothers selected through cluster sampling. Data were collected using validated questionnaires from July to August 2020 in Cianjur and Sukabumi districts, West Java Province, Indonesia. Descriptive statistics, chi-square, and multiple logistic regression were employed for data analysis. Results: The study revealed that 35.96% of teenage mothers experienced symptoms of postpartum depression. Among the variables studied, marriage satisfaction (p = 0.002), education level (p = 0.012), family income (p = 0.003), number of children (p = 0.044), and baby weight at birth (p= 0.0001) were significantly associated with postpartum depression. However, social support (p = 0.688) and religiosity (p = 0.788) showed no significant association with postpartum depression. Multiple logistic regression analysis further confirmed that marriage satisfaction (p = 0.001; OR = 0.365; 95% CI 0.197 - 0.676), family income (p = 0.001; OR = 0.326; 95% CI = 0.165 - 0.644), and the number of children (p = 0.026; OR = 3.68; 95% CI = 1.173 – 11.547) were the most significant factors associated with postpartum depression. Conclusion: The study highlighted a high prevalence of postpartum depression among adolescent mothers. Marital satisfaction, family income, and the number of children were identified as key factors associated with postpartum depression in this population. These findings emphasize the importance of considering these factors in nursing and midwifery practice to provide targeted support and interventions, ultimately improving the mental health outcomes for teenage mothers during the postpartum period.